2018
DOI: 10.2147/opth.s168033
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness after laser-assisted subepithelial keratomileusis and femtosecond LASIK: a prospective observational cohort study

Abstract: PurposeBased on the assumption that high levels of intraocular pressure (IOP) during femtosecond laser-assisted in situ keratomileusis (FS-LASIK) may compromise the retinal nerve fiber layer (RNFL), newer femtosecond platforms that operate without causing significant IOP elevation have been developed in recent years. However, this assumption has not been adequately tested. The aim of the current study was to evaluate possible changes in RFNL thickness in nonglaucomatous myopic patients undergoing FS-LASIK usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL remained unchanged [ 22 ]. Another study found that the RNFL was thicker 3 months after LASIK, especially in the inferior-temporal sector [ 23 ], which was similar to our results, but the possible mechanism is still not clear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL remained unchanged [ 22 ]. Another study found that the RNFL was thicker 3 months after LASIK, especially in the inferior-temporal sector [ 23 ], which was similar to our results, but the possible mechanism is still not clear.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL remained unchanged [22]. Another study found that the RNFL was thicker 3 months after LASIK, especially in the inferiortemporal sector [23], which was similar to our results, but the possible mechanism is still not clear. CT was observed thickened postoperatively [16], and there is research believing that CT was affected by ciliary muscle contraction, which may explain why LT thickened.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, research in children revealed that MT was thicker 1 day after surgery, but RNFL unchanged [22]. Another research found RNFL was thicker 3 months after LASIK, especially in the inferior-temporal sector [23], which was similar to our results, but the possible mechanism in it was still not clear.…”
Section: Discussionsupporting
confidence: 79%
“…In a previous study, intraoperative microkeratome LASIKs lead to IOP values of > 150 mmHg ( 9 ). Whilst FS-LASIKs leads to reduced IOP values during the suction, they lead to a greater period of maintenance of high IOP pressure, and there is uncertainty in comparative effect of FS-LASIKs on retinal measurements ( 10 ).…”
Section: Discussionmentioning
confidence: 99%